Carrot (Daucus carota L.) Growth and Yield at Various Doses of Chicken Manure - Arjunayanti Amir (Central Research Institute For Agriculture, 2022)
This research was in the form of an experiment that aims to determine the effect of chicken manure with the appropriate dose which can give the best effect on the growth and yield of carrots which was carried out in Buluballea Environment, Pattapang Village, Tinggimoncong District, Gowa Regency, South Sulawesi Province, took place from December 2011 until February 2012. This experiment was carried out using a randomized block design (RAK) consisting of one factor, namely the dose of chicken manure where there were six levels: 0 kg m-2; 0.4 kg m-2 ; 0.8 kg m-2 ; 1.2 kg m-2 ; 1.6 kg m-2 and 2 kg m-2 . Observations were made by taking plant samples at random, for one bed ten samples were taken. Observations included plant height, number of branching leaves, tuber length, tuber diameter, weight per tuber, weight per plot, weight per hectare and normal number of tubers. Observations were made once in two weeks after the plants were one month old. The application of chicken manure at a dose of 1.2 kg m-2 /12 tons ha-1 gave the best results on the growth and yield of carrots with a production of 30.33 tons ha-1.